Management and Outcomes of Breakage in Polyethylene-Ceramic Composite (Sandwich-type) Liners: Lessons From Long-term Follow-up - Daniel Rodríguez, MD; Thiago Carnaval, MD, MSc; Marcos-del-Carmen Rodríguez, MD; Antonio Coscujuela Maña, MD; José-Luis Agulló, MD, PhD; Sebastián Videla, MD, PhD (Arthroplasty Today, 2025)
This case series reports the only 3 instances of ceramic liner breakage among patients who underwent total hip arthroplasty (THA) with polyethylene–ceramic composite (sandwich-type) liners at our center between 1999 and 2002. Breakages occurred at approximately 6 (n = 2) and 17 years (n = 1) after the primary THA. Symptoms included audible crepitation, pain, and restricted motion during normal activities. Surgical revisions utilized a polyethylene liner and third-generation alumina ceramic head, with synovectomy and irrigation to remove debris (preventing third-body wear). All patients achieved good long-term outcomes. Although infrequent, the risk of breakage increases over time, and several patients still carry these liners years after THA. This case series underscores the importance of vigilant follow-up, patient education, and timely intervention to manage this infrequent but potentially catastrophic complication.